School-to-Work Transition in Comparative Perspective - Buttler, Dominik; Ławrynowicz, Maciej; Michoń, Piotr (Edward Elgar Publishing, 2023)
his is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Incisive and forward-thinking in its approach, this prescient book investigates the conditions of the often unstable school-to-work transition (SWT) period, calling for an improvement in labour market entry processes in order to facilitate the smooth integration of school leavers into employment. It captures the complex nature of SWTs by proposing and evaluating a new set of metrics which can act as a composite indicator of early employment security.